Plastic waste: impact on the planet’s ecosystem - Amirmatova, Konul; Aliyev, Elman (Journal of the Belarusian State University. Ecology, 2025)
Plastic waste, despite its versatility and wide range of uses, poses a serious threat to the planet’s ecosystem. Global plastic production increased from 1.5 million tonnes in 1950 to 335 million tonnes in 2016. Although recycling rates for plastic products are increasing, much of the remainder is still discarded into the environment. Initially, public attention was mainly focused on large plastic waste. In the past few years, small plastic fragments, especially microplastics, have become increasingly concerned due to their pollution and environmental risks. They have a negative impact on environmental components and the health of living organisms, including humans. It is estimated that plastic makes up to 54 % (by weight) of anthropogenic waste discarded into nature. This waste often accumulates in various ecosystems such as oceans, rivers, soils and even the air. Urbanization, rapid economic development and population growth contribute to the increase in plastic pollution, which worsens the global environmental situation. The problem of plastic pollution was first recorded in 1960, when plastic particles were found in the intestines of seabirds. Since then, the situation has only worsened; today, microplastics are ubiquitous in the seas, beaches, soils, rivers, lakes and air. Moreover, plastic particles have even been found in drinking water in countries such as Germany, Norway, the United States, China and elsewhere, highlighting the global scale of the problem. This article reviews the literature on the sources of microplastics in the atmosphere, hydrosphere and soil. It also assesses their prevalence in ecosystems in the form of waste of various shapes, sizes and colours. Particular attention is paid to the negative impacts of microplastics on living organisms such as fish, sea turtles and birds. In addition, positive steps aimed at reducing pollution are discussed: recycling, using eco-friendly materials and raising public awareness.